STUDIES ON LONG WING TRAWL FOR SHRIMPS Off KAKINADA (A. P.) COAST (i) RESULTS OF COMPARATIVE FISHING EXPERIMENTS WITH THE CONVENTIONAL TWO SEAM TRAWL - SATYANARAYANA, A V.V; NARAYANAPPA, G; DAWSON, PERCY (Fishery Technology, 2017)
Comparative fishing operations with the conventional two seam net and a 29.26 m. long wing shrimp trawl of four seam type were undertaken. The result showed that the four seam net gave nearly twice prawn catch than that of the conventional type. It was also found that the four seam net can be developed into a combination trawl for the effective exploitation of both prawns and fish along the coasts off Kakinada.